2012
DOI: 10.1080/09593330.2012.671371
|View full text |Cite
|
Sign up to set email alerts
|

Decolourization of melanoidins by a electrocoagulation process using aluminium electrodes

Abstract: The decolourization ofmelanoidins was studied with a batch electrocoagulation (EC) process using aluminium electrodes. The effects of conductivity (K = 500-3000 microS/cm), initial pHi (4.2-8.2), current density (j = 2.5-7.5 A/m2), initial melanoidin concentration (C0 = 100-800 mg/L) and operating time (tEC = 0-60 min) were investigated on the decolourization efficiency. The results obtained from the EC process were extremely efficient and able to achieve a decolourization efficiency of > 98% at pHi = 4.2, j =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…pH i is also one of the most important parameters influencing the production of metal species at the anode, the production of hydroxyl ions at the cathode, and the chemical structure of the wastewater . When an Al electrode was used, monomeric species such as Al(OH) 2+ , normalAlfalse(normalOHfalse)2+, normalAl2(OH)24+, and Al(OH) 4− and polymeric species such as normalAl6(OH)153+, normalAl7(OH)174+, normalAl8(OH)204+, normalAl13normalO4(OH)247+, and normalAl13(OH)345+ were formed during the EC process .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…pH i is also one of the most important parameters influencing the production of metal species at the anode, the production of hydroxyl ions at the cathode, and the chemical structure of the wastewater . When an Al electrode was used, monomeric species such as Al(OH) 2+ , normalAlfalse(normalOHfalse)2+, normalAl2(OH)24+, and Al(OH) 4− and polymeric species such as normalAl6(OH)153+, normalAl7(OH)174+, normalAl8(OH)204+, normalAl13normalO4(OH)247+, and normalAl13(OH)345+ were formed during the EC process .…”
Section: Resultssupporting
confidence: 93%
“…In this study, the pH of the wastewater was increased during the EC process and the maximum removal efficiencies occurred at pH i 4–6 (Figures and ). These results are consistent with literature studies in which coprecipitation and adsorption were suggested as two significant interaction mechanisms during the process. The pH ranges of wastewater were found to be effective for both mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Al 3+ ion generation occurs at the anode surface, whereas hydrogen gas transpires at the cathode surface. Flocs of Al(III) hydroxides and polyhydroxy species formed during coagulation, and the organic pollutants are removed from the aqueous phase via charge neutralisation, adsorption and sweep flocculation [16]. The flocs can then be separated by sedimentation or/and flotation [12].…”
mentioning
confidence: 99%